A time‐efficient method to determine parameters for measurement of short‐interval intracortical inhibition for quadriceps. (25th July 2020) - Ruas, Cassio V.; Taylor, Janet L.; Nosaka, Kazunori; Haff, G. Gregory; Latella, Christopher
Abstract: Short‐interval intracortical inhibition (SICI) is often assessed to investigate inhibitory responses in the primary motor cortex representation of the quadriceps. However, determining appropriate paired‐pulse transcranial magnetic stimulation (TMS) parameters to optimise SICI measurement can be impractical and time‐consuming. This study investigated the intensity required to elicit maximal and 50% of maximum inhibition, and the test‐retest reliability of a time‐efficient approach for SICI measurement in quadriceps. Nine men and six women (26.6 ± 4.4 years) underwent single and paired‐pulse (3‐ms interval) TMS during 10% maximal voluntary isometric contraction on two days. Responses were recorded from vastus lateralis (VL), rectus femoris (RF) and vastus medialis (VM). Test stimulus intensity was 140% of active motor threshold (AMT), and conditioning stimulus intensities (CSIs) ranged from 55% to 90% (eight intensities) of AMT (five test and five paired responses for each intensity). With CSI of 55% AMT, SICI was minimal (conditioned:test motor evoked potential [MEP]; 1.00, 0.96 and 0.95 for VL, RF and VM, respectively, <1.00 indicates inhibition). Inhibition was greater at 70%–90% AMT for VL (0.67–0.85), at 75%–90% AMT for RF (0.70–0.78) and at 80%–90% AMT for VM (0.59–0.68) when compared to 55% AMT. The CSIs that elicited maximal and 50% maximal inhibition were 84% and 75% AMT, respectively. Reliability for individual CSIs ranged from "poor‐to‐good" for all muscles. SICI averaged across all CSIs demonstrated "moderate" reliability for VL and VM, but "poor" reliability for RF. This method may offer a practical approach to individualise and select CSIs to investigate quadriceps inhibitory networks in neurophysiological studies. Abstract : A time‐efficient method was used to individualise short interval intracortical inhibition (SICI) for quadriceps. The between‐day reliability of individual conditioning stimulus intensities (55%–90% of active motor threshold [AMT]) ranged from "poor‐to‐good" across muscles, and intensities that elicited maximal and 50% of maximal inhibition were 84% and 75% AMT, respectively. This method may offer a practical approach to investigate quadriceps inhibitory networks in neurophysiological studies.